PENINGKATAN KEMAMPUAN REPRESENTASI DAN KONEKSI MATEMATIS SERTA KEMANDIRIAN BELAJAR MAHASISWA MELALUI MODEL PROJECT-BASED LEARNING BERBANTUAN GEOGEBRA - Ari Septian, - (2021)
This study aims to examine the achievement and improvement of mathematical representation abilities, mathematical connection abilities, and student self-regulated learning through a project-based learning model assisted by Geogebra. The research method used was a quasi-experimental design with a pretest-posttest nonequivalent multiple group design. The population is students of the Mathematics Education Study Program at University in West Java. Class 1A and 1B were the samples in this study. The data analysis technique used independent sample t test, Mann Whitney test, two-way ANOVA test, Kruskal Wallis test, descriptive, and contingency association test. The results showed that: (1) the achievement and improvement of the mathematical representation abilities of students who obtained the project-based learning model assisted by Geogebra were better than students who obtained the project-based learning model; (2) there is no interaction effect of learning models and cognitive styles on the achievement of students' mathematical representation abilities. however, there is an interaction effect of learning models and cognitive styles on the improvement of students' mathematical representation abilities; (3) the achievement and improvement of students' mathematical connection skills who obtained the Geogebra-assisted project-based learning model was better than students who obtained the project-based learning model; (4) there is no interaction effect of the interaction of learning models and cognitive styles on the achievement and improvement of students' mathematical connection abilities; (5) the achievement of self-regulated learning who received the project-based learning model assisted by Geogebra was better than students who obtained the project-based learning model; (6) there is no interaction effect of learning models and cognitive styles on the achievement of student self-regulated learning; (7) the achievement of the mathematical representation ability indicators of students who obtained the Geogebra-assisted project-based learning model was categorized as good. Meanwhile, students who obtained the project-based learning model were categorized as sufficient; (8) the achievement of the mathematical connection ability indicators of students who obtained the Geogebra-assisted project-based learning model was categorized as good. Meanwhile, students who obtained the project-based learning model were categorized as sufficient; (9) achievement indicators of self-regulated learning who apply the project-based learning model assisted by Geogebra and students who apply the project-based learning model are categorized as good; (10) there is no significant association between representation ability and mathematical connections of students who get a project-based learning model assisted by Geogebra; (11) there is a significant association between self-regulated learning and the mathematical representation ability of students who obtain a project-based learning model assisted by Geogebra; and (12) there is a significant association between self-regulated learning and the mathematical connection ability of students who obtain a project-based learning model assisted by Geogebra.